OPERATIONS STRATEGY AND MANUFACTURING FLEXIBILITY (Approach for Operational Excellence) - Timilsina, Binod (My University, 2013)
Due to the rapid change in business environment importance of manufacturing flexibility and continuous improvement in operations strategy has become a mandatory for obtaining operations excellence. The main purpose of the study is to see the impact of company size on managers thinking at different attributes of market requirements and manufacturing flexibility. The effort has been given to cover all possible theory under each topic, so that the reader can get a clear picture of manufacturing flexibility, operations strategy and operational excellence, along with the ways to implement them in operational level.This research is hoped to be useful for those who further desire to explore in this field of study. It is also assumed to be beneficial for manufacturing industry in obtaining operational excellence.
Keywords: Flexibility; operations strategy; operational excellence; fi=Tuotantotalous|en=Industrial Management|; fi=Master's Degree Programme in Industrial Management|